Challenges in diagnosing bovine tuberculosis through surveillance and characterization of Mycobacterium species in slaughtered cattle in Kolkata - Molla Zakirul Haque; Chanchal Guha; Ayan Mukherjee; Sukhen Samanta; Partha Sarathi Jana; Ujjwal Biswas; Sangeeta Mandal; Santanu Pal; Manigandan Venkatesan; Joy Sarojini Michael; Pramod Kumar Nanda; Samiran Bandyopadhyay; et al. (BMC Veterinary Research)
Abstract Background Tuberculosis in cattle is caused by Mycobacterium tuberculosis complex (MTBC) species. Apart from MTBC, different Nontuberculous Mycobacteria (NTM) species have also been isolated from cattle. The presence of NTM infection in bovines makes the diagnosis of bovine tuberculosis (bTB) a cumbersome task. Therefore, a cross sectional study was conducted to isolate and characterize different Mycobacterium spp. from a slaughterhouse situated in Kolkata, a city in the eastern part of India. Results Out of 258 morbid samples, 98 isolates were found to be positive for bacterial growth, and 35% (n = 34) were positive for Mycobacterium. 94% of Mycobacterial cultural isolates were NTM (n = 32), and the rest (n = 2) were found to be MTBC. Species-level identification of the isolates by hsp65 sequencing revealed that out of 32 isolates, 24 were M. fortuitum, three were M. abscessus, two each were M. chelonae and M. parascrofulaceum, and one was M. novocastrense. A phylogenetic tree with partial hsp65 gene sequences was also constructed to determine the relatedness of the unknown isolates to the reference strains. Conclusion Both NTM species and MTBCs were identified from TB-like lesions in cattle that were slaughtered at the Kolkata abattoir. This discovery may indicate that NTM contributes to the development of lesions in cattle. Also, we recommend implication of more specific diagnostic tests for bTB.